The Power of the Brush - Hwisang Cho (University of Washington Press, 2020)
The invention of an easily learned Korean alphabet in the mid-fifteenth century sparked an "epistolary revolution" in the following century as letter writing became an indispensable daily practice for elite men and women alike. The amount of correspondence increased exponentially as new epistolary networks were built among scholars and within families, and written culture created room for appropriation and subversion by those who joined epistolary practices.